Pemanfaatan Aplikasi TikTok sebagai Media Pembelajaran Interaktif dalam Mata Pelajaran Sosiologi - Dita Iqlima; Anik Widiastuti; Agustina Tri Wijayanti; Saliman Saliman (Jurnal Ilmiah Global Education, 2026)
This study discusses the use of the TikTok application as an interactive learning medium in sociology subjects. The TikTok application has an important role as an interactive learning medium. The purpose of this study is to determine the use of the TikTok application as an interactive learning medium in sociology subjects and to determine how the TikTok application can build students' abilities and understanding in linking material to community life. The method used is a descriptive qualitative research method. Data were collected through observation and interview techniques. Based on the results of the study, the TikTok application is very helpful for students in understanding the concept of sociology material and its relationship to life in society. The TikTok application can also build students' abilities and understanding in understanding material and linking material to life in society by looking at current phenomena in the TikTok application, both political, social, and cultural issues at home and abroad. The existence of the TikTok application helps students construct knowledge through understanding and experience gained by students themselves.